2016
DOI: 10.13031/trans.59.11631
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biochar from Rice Hulls and Wood Chips Produced in a Top-Lit Updraft Biomass Gasifier

Abstract: ABSTRACT. The objective of this study was to characterize biochar produced from rice hulls and wood chips in a top-lit updraft gasifier. Biochar from four airflows (8, 12, 16, or 20 L min -1 ) and two insulation conditions (not insulated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Varela Milla et al [26] also reported the greatest surface area for wood biochar than for RH biochar. SSA-BET of CWB is in accordance with the results reported by James et al [27], which attributed a surface area over 400 m 2 g −1 for wood chips biochar. SSA-BET of RHB are similar to the obtained results of RHB produced at 650 • C by Pariyar et al [28] and produced at 800 • C by Jindo et al [29], which indicate that applying a higher temperature to this material would not result in higher SSA-BET.…”
Section: Discussionsupporting
confidence: 91%
“…Varela Milla et al [26] also reported the greatest surface area for wood biochar than for RH biochar. SSA-BET of CWB is in accordance with the results reported by James et al [27], which attributed a surface area over 400 m 2 g −1 for wood chips biochar. SSA-BET of RHB are similar to the obtained results of RHB produced at 650 • C by Pariyar et al [28] and produced at 800 • C by Jindo et al [29], which indicate that applying a higher temperature to this material would not result in higher SSA-BET.…”
Section: Discussionsupporting
confidence: 91%
“…This result also suggested that more volatiles were lost with increasing air intake and holding times due to the higher temperature and longer pyrolysis reaction time. This phenomenon is similar to that explored in the study by James et al [32], in which the volatile matter of wood chip biochar decreased from 31.8% to 6.6% when the airflow increased. It is typically associated with the release of more volatiles as a result of an increase in reaction temperature and rising airflow in a top-lit updraft gasifier.…”
Section: Proximate Analysissupporting
confidence: 89%
“…According to the data presented in Table 7 , the best of the obtained biochars (MS400 sample) shows favorable energy parameters not only in comparison to commercial products but also to carbon materials prepared from a various kinds of biomass. It is clearly inferior only to biochars prepared from groundnut shells [ 36 ], coconut and palm shells [ 37 ], as well as wood chips [ 38 ], for which the HHV value is 45.2, 33.7, 33.6 and 33.2 MJ/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%